In Search of Principles of Visegrad (Economic) Cooperation and its Inspiration for Bilateral Relations between North Macedonia and Bulgaria - Vit, Michal (Identities: Journal for Politics, Gender and Culture, 2023)
This paper examines the economic cooperation within the Visegrád Four (V4) in the context of EU membership and its potential inspiration for bilateral relations between North Macedonia and Bulgaria. It explores the alignment of political values and economic relations in the V4, highlighting the EU’s role in fostering cross-border collaboration. The analysis delves into the shared priorities of the V4 towards EU enlargement and how these experiences can guide Western Balkan countries. It discusses the transformation of economic cooperation in the V4, emphasizing the strategic role of Germany and the evolution of regional dynamics. The paper also analyzes the challenges and limitations in applying the V4 model to Bulgarian-North Macedonian relations, considering the differences in historical experiences, economic convergence, and the impact of EU-driven Europeanization. It concludes by assessing the unique nature of bilateral relations in the context of EU integration and enlargement, emphasizing the need for a distinct approach for effective collaboration between Bulgaria and North Macedonia. Author(s): Michal Vit Title (English): In Search of Principles of Visegrad (Economic) Cooperation and its Inspiration for Bilateral Relations between North Macedonia and Bulgaria Journal Reference: Identities: Journal for Politics, Gender and Culture, Vol. 20, No. 1-2 (2023). Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 32-39 Page Count: 8 Citation (English): Michal Vit, "In Search of Principles of Visegrad (Economic) Cooperation and its Inspiration for Bilateral Relations between North Macedonia and Bulgaria,” Identities: Journal for Politics, Gender and Culture, Vol. 20, No. 1-2 (2023): 32-39.